PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS EDUCATION GAME SEBAGAI MEDIA PEMBELAJARAN KIMIA - Heriyanto, Aris; Haryani, Sri; Rahayu S., Sri Mantini (Universitas Negeri Semarang, 2014)
This research aims to develop an MPI based on an education game as a media of chemistry learning media.This research is constructed with the research design of Research and Development (R & D) with the stages of problem and potential identification, data collection, product design, design validation, product revision, product testing, revision of the design, testing and revision of product usage, so that the final product is produced. This research examines the characteristics and effectiveness of MPI based education game on learning games on colloidal system in high school. media characteristics is achieved on MPI processes based education game, whereas the effectiveness is measured by students indicator who reach the score ? 75 to 75% of total students, students who have a good interest reach 75% of total students, and students who have very high activity reach 75% of total students. The Results of this research is that the characteristics of MPI-based education game is an interactive computer-assisted learning media which is designed for high school students and teachers in the learning the material of colloid system which emphasise on education game, that is packaged in a CD learning with Executable format (*. Exe) and Shockwafe Flah Object (*. swf). At the pilot usage, it is found that all the effectiveness criteria are achieved. In addition, the responses of students and teachers of the MPI-based education game show a very good responses. Based on the results of the research and discussion, it can be concluded that MPI-based education games is effective and proper for use as a learning medium of chemistry.